Overview of the development of speaker recognition. Issue 1 (March 2021) - Yuan, Xinyu; Li, Guanyu; Han, Jiao; Wang, Di; Tiankai, Zhi
Abstract: Speaker recognition is a technology that recognizes a person's identity through a person's voice. Speaker recognition is one of the important research topics in the field of biometrics. This article first introduces the background and research significance of speaker recognition; secondly, it briefly introduces speaker recognition technology; again introduces the method research used in speaker recognition; and finally analyzes the research difficulties and challenges of speaker recognition.